PEMANFAATAN HASIL BUMI BIJI NANGKA UNTUK PEMBUATAN BROWNIES OLEH MASYARAKAT DESA KEBON HUI BANDUNG BARAT - Rochiyat Setiawan; Tri Yuni Susilowati (Eduturisma, 2024)
This research focuses on the problem of the right recipe for making steamed brownies with jackfruit seed and the unknown interest in steamed brownies with jackfruit seed among communities. Data collection techniques are divided into two, namely primary data and secondary data. Primary data was obtained using the observation method based on facts in the field during the author's field work, while secondary data was obtained from literature study. The results of the descriptive research showed that making brownies was made from jackfruit seed by experimenting methode 3 times, with a ratio of jackfruit seed and wheat flour of 50%-50%, 65%-35% and 100% using jackfruit seed . In the third experiment, steamed bownies had the perfect taste, aroma, color and texture. From the results of the questionnaire of 30 respondents, in terms of taste, 60% liked it, 30% really liked it, in terms of aroma, 56.7% liked it, 36.7% really liked it, in terms of color, 67% liked it, 23% really liked it, in terms of texture, 53% liked it, 30% really liked it.